A plataforma “Rede Pública” e o futuro da TV interativa no Brasil: uma proposta para o Governo Federal na era da TV 3.0 - Silva, Bárbara Hellen Padilha da; Silva, Wesley Alves da; Riquelme, Maristela de Freitas; Pereira, Clarissa Evelin; Aguiar, Gabriel Silva; Freitas, Herick José de; Becker, Valdecir (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2025: Anais Estendidos do XXXI Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2025.16802, 2025)
This article presents the conception and development of the Rede Pública platform, a proposal based on TV 3.0 that seeks to integrate content from Brazilian public broadcasters with digital government services. The initiative is part of the evolution of the Brazilian Digital Television System (SBTVD), which incorporates the convergence between broadcast and broadband. The project was structured through requirements elicitationworkshops with government agencies, using the Design Thinking methodology to ensure adherence to public and social demands. Interactive prototypes were developed in Figma, including both the unified television platform and a second-screen application, which expands the possibilities of user engagement and mobility. The results highlight the potential of TV 3.0 as a strategic resource to strengthen digital citizenship, promoting inclusion, usability, and accessibility, as well as establishing a reference model for future national initiatives. As future work, the expansion of tests with real and diverse users is foreseen, in order to validate the user experience and consolidate interactive TV as an instrument of integration between the State and society.